2019
DOI: 10.33259/jlivestsci.2019.114-117
|View full text |Cite
|
Sign up to set email alerts
|

Use of Thistle meal (Silybum marinum) as additive to improve nutritional and protective qualities of sausages.

Abstract: Thistle meal is characterized by a high content of dry matter and protein, which causes its use as a protein food additive. In addition, thistle meal is characterized by a high content of structural fibrous carbohydrates of fiber, hemicellulose and pectin substances that allows to adsorb heavy metals and remove them from the gastrointestinal tract. The research aims to study the possibility of thistle meal introduction into the formulation of Bavarian sausages to increase their consumer and protective properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In the course of the experiment, it was found that versus control, due to the highest growth rate, the meat chickens in the second experimental group consumed mixed feed 9.00% less per unit of received gross formation. It shows that the best dose of Epofen feeding by reducing the risk of T-2 toxicosis in broiler-chickens is 200 g/t feed, which improves the basic economic and useful qualities (Dzhaboeva et al, 2019;Kennedy et al, 2019) To ensure high growth rate for broiler chickens, especially at the risk of mycotoxicosis, the problem of increasing the activity of digestive enzymes is of paramount importance, so we studied the effect of different antioxidant doses on the enzymes activity in the content of the muscular stomach (Table 4) and duodenum ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…In the course of the experiment, it was found that versus control, due to the highest growth rate, the meat chickens in the second experimental group consumed mixed feed 9.00% less per unit of received gross formation. It shows that the best dose of Epofen feeding by reducing the risk of T-2 toxicosis in broiler-chickens is 200 g/t feed, which improves the basic economic and useful qualities (Dzhaboeva et al, 2019;Kennedy et al, 2019) To ensure high growth rate for broiler chickens, especially at the risk of mycotoxicosis, the problem of increasing the activity of digestive enzymes is of paramount importance, so we studied the effect of different antioxidant doses on the enzymes activity in the content of the muscular stomach (Table 4) and duodenum ( Table 5).…”
Section: Resultsmentioning
confidence: 99%